The Central Java Province Case Study: The Function of Entrepreneurial Marketing During the Covid-19 Pandemic - Frans Sudirjo (Pusat Riset dan Inovasi Nasional, 2023)
The entrepreneurial marketing method is a strategic option that business micro small medium enterprises players might use to survive, particularly in the face of the Covid-19 pandemic. The purpose of this research is to determine which entrepreneurial marketing factors are crucial in enhancing business micro small medium enterprises customer satisfaction in the creative economy business during the Covid-19 pandemic. This study specifically investigates whether the elements of entrepreneurial marketing such as proactiveness, opportunity-focused, risk-taking orientation, innovation-oriented, customer intensity, resource leveraging, and value creation have an effect on customer satisfaction. An online survey method was used to obtain primary data from 249 business micro small medium enterprises in the creative economy industry in Central Java who were conducting their enterprises before and during the Covid-19 pandemic. The sample approach includes nonprobability sampling via the purposive sampling methodology.